Expression of Tim-3 in peripheral blood mononuclear cells and placental tissue in unexplained recurrent spontaneous abortion. Issue 38 (September 2018) - Zhuang, Xuewei; Xia, Xiyan; Liu, Lingxiao; Zhang, Yi; Zhang, Xin; Wang, Chuanxin
Abstract : Abstract: The expression of T-cell immunoglobulin domain, mucin domain-3 (Tim-3) in unexplained recurrent spontaneous abortion (URSA) was investigated. Tim-3 mRNA expression in peripheral blood mononuclear cells (PBMCs) of URSA and control groups was assayed by fluorescent quantitative real-time polymerase chain reaction. Tim-3 protein expression intensity and localization in placental villi and uterine decidua were determined using immunohistochemical assay. The CD4 + Tim-3 + /CD4 + cell ratio in PBMCs was determined by flow cytometry. Tim-3 mRNA expression in PBMCs was significantly higher in URSA than in normal controls (1.32 ± 0.25 vs 1.20 ± 0.12, P <  .05). Tim-3 was expressed in placental tissue from both URSA patients and normal pregnant females (controls); however, the expression intensity was higher in the URSA group (0.54 ± 0.31 vs 0.35 ± 0.22, P <  .05). CD4 + Tim-3 + /CD4 + cell ratio in PBMCs was significantly higher in the URSA group than that in the control group (4.53 ± 1.66% vs 1.28 ± 0.71%, P <  .05). Increased Tim-3 expression in PBMCs and placental tissue of URSA might affect maternal-fetal immune tolerance. Tim-3 was involved in the pathogenesis of URSA, which was expected to serve as an indicator for the immune evaluation of URSA.